Legal Linguistics of Judicial Educational Activities - О. V. Minchenko (Bulletin of Kharkiv National University of Internal Affairs)
The objective of the study is to provide characteristics to the state of academic discipline “Legal Linguistics” in Ukraine and in the countries of Romano-Germanic law, and its origin. To achieve the objective, the author has solved the following tasks: 1) description of the state of academic discipline “Legal Linguistics” in Ukrainian educational institutions; 2) “Legal Linguistics” as an academic discipline and as a research direction in the educational institutions of Germany and Switzerland and its importance for training a “European lawyer”.